Advances in Therapeutic Strategies for Fibrodysplasia Ossificans Progressiva: From Symptom Management to Targeted Therapies - Binnar, Rutuja Sudam; Patil, Rahul Nimba; Shaikh, Mohammad Rizwan Niyazuddin (Asian Journal of Biological and Life Sciences, 2026)
Muscles, tendons, and ligaments are part of the soft tissues that can develop progressive heterotopic ossification in Fibrodysplasia Ossificans Progressiva (FOP), a very rare genetic disorder that follows an autosomal dominant pattern. About one in every two million people worldwide are affected by this condition. Because FOP can resemble other disorders such as sarcoma, fibromatosis, and congenital skeletal abnormalities, early diagnosis is often challenging. Current management mainly focuses on symptomatic treatment, including the use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) or COX-2 inhibitors for pain relief and short-term corticosteroids during acute flare-ups. The aim of this review is to summarize current understanding of the molecular basis of FOP, particularly the role of ACVR1 mutations, and to evaluate existing supportive treatments along with emerging targeted and gene-based therapeutic strategies that may help slow disease progression.
Keywords: ACVR1 gene mutation; Heterotopic Ossification (HO); Palovarotene; Fibrodysplasia; Ossificans Progressiva (FOP)